Gender Diversity Effect on Tax Avoidance and Firm Risk - Sofianty, Diamonalisa; Murwaningsari, Etty; Mulyani, Susi Dwi (Technium Social Sciences Journal, 2022)
The purpose of this study was to examine the effect of gender diversity on firm risk with tax avoidance as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study used SPSS version 20.0 to process the data. The sample of this research is 51 manufacturing companies listed on the IDX using multiple regression panel data. This study uses financial statement data for the 2015 – 2019 period. The findings of this study are (1) there is a negative effect of gender diversity on tax avoidance; (2) there is a negative effect of gender diversity on firm risk; (3) there is a positive effect of tax avoidance on firm risk; (4) Gender diversity has an influence on firm risk through tax avoidance. The limitations of this study are as follows: the research sample is only in manufacturing companies listed on the Indonesia Stock Exchange with a limited number of samples because during the observation period there are companies that are losing, suspending, and delisting. Therefore, this research suggests that (1) Further research can expand the scope of the research sample or compare it with companies in other industrial sectors. (2) Further research can increase the number of other variables, such as Corporate Social Responsibility by using the Blau-Index measurement (1975) so that the measurement can be more detail and constructive. (3) Further research can use other samples in Asean countries by comparing the success rate of anti-corruption disclosure in ASEAN countries. The practical implications include the following: (1) the role of gender diversity in the company is very necessary for implementing Good Corporate Governance (GCG) thus a healthy company will be created so that the company's risk does not occur in the future. (2) the role of the government is needed in making policies so that companies do not do tax evasion. The originality of the research includes this study, which is the first to analyze gender diversity on firm risk through tax avoidance.